Cost-effectiveness of hypertension treatment: a population-based study - Costa, Juvenal Soares Dias da; Fuchs, Sandra Costa; Olinto, Maria Teresa Anselmo; Gigante, Denise Petrucci; Menezes, Ana Maria Baptista; Macedo, Silvia; Gehrke, Sabrina (São Paulo Medical Journal, 2002)
CONTEXT: The cost-effectiveness of the treatment of hypertension has scarcely been investigated in population-based studies. Most data come from secondary analysis of clinical trials and administrative sources. OBJECTIVE: To describe the healthcare costs for outpatient hypertension treatment in comparison with diabetes mellitus and chronic bronchitis, and to examine the cost-effectiveness of different classes of antihypertensive drugs. DESIGN: Cross-sectional population-based study. SETTING: Urban area of Pelotas, southern Brazil. PARTICIPANTS: Individuals aged 20-69 years, identified through multi-stage probability sampling. METHODS: Participants were interviewed at home. Demographic data, education, income, smoking, previous morbidity, use of medicine and other characteristics were assessed via a pre-tested questionnaire, and blood pressure while seated was measured in a standardized way. RESULTS: Approximately 24% of the participants had high blood pressure or were taking antihypertensive drugs, and among these, 33% had had a physician consultation during the month preceding the interview. The monthly mean costs of care for hypertension (R$ 89.90), diabetes (R$ 80.64) and bronchitis (R$ 92.63) were similar. Treatment of hypertension consumed 22.9% of the per-capita income, corresponding to R$ 392.76 spent per year exclusively on antihypertensive drugs. Most of the direct costs associated with hypertension and diabetes were spent on drugs, while patients with bronchitis had greater expenditure on appointments. The cost-effectiveness relationship was more favorable for diuretics (116.3) and beta blockers (228.5) than for ACE inhibitors (608.5) or calcium channel blockers (762.0). CONCLUSION: The costs of hypertension care are mainly dependent on the expenditure on blood pressure-lowering drugs. Treatment of hypertension with diuretics or beta blockers was more cost-effective than treatment with ACE inhibitors and calcium channel blockers.